PERSPECTIVES OF INNOVATION IN SERBIAN FIRMS - EMPIRICAL EVIDENCE FROM AGRO-FOOD AND SOFTWARE INDUSTRY - Mosurović Ružičić, Marija; Kutlača, Đuro; Stanišić, Nenad; Semenčenko, Dušica (Economics of Agriculture, 2018)
Based on the available literature on theory of innovation and the data processed from the official research on innovation activities in Serbian firms, this paper shows different perspectives of usage of the innovation activities indicators. The results showed that firms involved in software sector are more innovative than firms in agro food sector. On the basis of the research conducted in this paper, it is possible to draw conclusions which are significant to the management of enterprises in observed industries. According to these recommendations, innovative enterprises management could respond to problematic situation of business economy in the field of innovation management through adequate business strategies. Besides that, empirical research in innovative activities in Serbia in the two observed sectors yield a serious analytic framework to guide industrial policy and employ appropriate measures in order to improve national competitiveness based on knowledge.